An Anthropometric-Based Subject-Specific Finite Element Model of the Human Breast for Predicting Large Deformations - Pianigiani, Silvia; Ruggiero, Leonardo; Innocenti, Bernardo (Frontiers in Bioengineering and Biotechnology, 2015)
The large deformation of the human breast threatens proper nodules tracking when the subject mammograms are used as pre-planning data for biopsy. However, techniques capable of accurately supporting the surgeons during biopsy are missing. Finite Element (FE) models are at the basis of currently investigated methodologies to track nodules displacement. Nonetheless, the impact of breast material modeling on the mechanical response of its tissues (e.g. tumors) is not clear. This study proposes a subject-specific FE model of the breast, obtained by anthropometric measurements, to predict breast large deformation. A healthy breast subject-specific FE parametric model was developed and validated by Cranio-caudal (CC) and Medio Lateral Oblique (MLO) mammograms. The model was successively modified, including nodules, and utilized to investigate the effect of nodules size, typology and material modeling on nodules shift under the effect of CC, MLO and gravity loads. Results show that a Mooney-Rivlin material model can estimate healthy breast large deformation. For a pathological breast, under CC compression, the nodules displacement is very close to zero when a linear elastic material model is used. Finally, when nodules are modeled including tumor material properties, under CC or MLO or gravity loads, nodules shift shows ∼15% average relative difference.